E ffect of supplementation of Typha domingensis Pers. fruit powder and aqueous extract on productive performance and some physiological characteristics of broiler chickens - Abbas, R. J.; Sukkar, S. T. (Diponegoro University, 2026)
This study evaluated the effects of dietary supplementation with Typha domingensis Pers. fruit flour (TDF) and its aqueous extract (TDE) on growth performance, physiological responses, and gut microbial balance in broiler chickens. A total of 216 one-day-old chicks were allocated at seven days of age into six treatment groups. Birds received either a basal diet (T1, control), TDE supplementation in drinking water at 5 or 15 mL/L (T2 and T3), TDF inclusion in feed at 5 or 15 g/kg (T4 and T5), or a combined supplementation of TDF and TDE at 7.5 units each (T6). Supplemented groups exhibited significant improvements (p ≤ 0.05) in final body weight, body weight gain, feed conversion ratio, pro-duction index, performance index, and economic efficiency compared with the control group. Addi-tionally, the relative weight of the bursa of Fabricius increased, whereas abdominal fat deposition de-creased. Blood biochemical analysis revealed significant reductions in serum cholesterol, triglycerides, low-density lipoprotein (LDL), aspartate aminotransferase (AST), and alanine aminotransferase (ALT), accompanied by increased high-density lipoprotein (HDL) levels. Antioxidant status was enhanced, as indicated by elevated superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) activities. Microbiological assessment demonstrated reduced total bacterial counts and Escherichia coli, along-side increased populations of beneficial Lactobacillus spp. In conclusion, supplementation with TDF and TDE positively influenced growth performance, metabolic health, antioxidant capacity, and intesti-nal microbial balance in broiler chickens, suggesting their potential as natural feed additives to improve poultry productivity and health.